The importance of line as an essential element in the art and creating a figurative painting - أحمد, نجوى (Latakia University Journal -Engineering Sciences Series, 2025)
Great changes arise as a result of scientific and technical progress in the system of performing artistic works for their functions, and the media have also improved, in a way that has shown huge potential for establishing communication between the recipient and the art, and therefore there is a radical change occurring in the relationship between art and the viewer, towards intellectual, cultural, and visual richness, therefore It was necessary to pay attention to the construction of the pictorial painting, its basic components, and its elements that begin with the dot, and the effect resulting from its movement in several directions. It leaves an impact represented by the lines responsible for harvesting the spaces, or the void on the surface of the painting, to compose the vocabulary of the plastic visual text of bodies, shapes, The blocks are composed within purposeful artistic formations, that is, formations that are visually studied to attract the viewer to the artistic work. Studying the formations means understanding the foundations of placing the parts so that the whole is composed. Line is considered an element of composition that has an important and major role in building the artistic work, as hardly any artistic work is devoid of it, although to varying degrees. It is the oldest form of human expression, and a rhythmic journey in a system based on diversity in the shapes of lines and their directions, when they extend and bend, curve or color, thin or thick, rough or smooth…..etc. Due to the strength of the line element in expression and its aesthetics; It was not limited to being an external line defining shapes and blocks, but rather it became an independent value in Itself.